Slovenske dramatičarke v 21. stoletju - Pezdirc-Bartol, Mateja (Slavistična revija, 2016)
Despite the fact that the earliest Slovene women writers, Luiza Pesjak and Zofka Kveder, wrote plays, women playwrights have been a rarity throughout Slovene literary history. In the new millennium, however, there has been a noticeable breakthrough of women playwrights, whose work is created and developed in close connection with their hands-on work in theatres. The analysis of 37 texts by 15 authors shows that the modern Slovene women playwrights focus on women's position in family and society, as well as on the problems of modern society and global issues. The texts also show an awareness that the dramatic form is going through a crisis; the authors address the problem of the plays' status, and research unconventional ways of playwriting.
Keywords: postdramatic theatre; postdramsko gledališče; Potočnjak, Draga, 1958-; Semenič, Simona, 1975-; Slovene drama; Slovene literature; Slovene women playwrights; slovenska dramatika; slovenska književnost; slovenske dramatičarke